2010
DOI: 10.1002/jmv.21974
|View full text |Cite
|
Sign up to set email alerts
|

Full genomic analysis of a G8P[1] rotavirus strain isolated from an asymptomatic infant in Kenya provides evidence for an artiodactyl‐to‐human interspecies transmission event

Abstract: Group A rotavirus (GAR) G8P[1] strains, found sometimes in cattle, have been reported rarely from humans. Therefore, analysis of the full genomes of human G8P[1] strains are of significance in the context of studies on interspecies transmission of rotaviruses. However, to date, only partial-length nucleotide sequences are available for the 11 genes of a single human G8P[1] strain, while the partial sequences of two other strains have been reported. The present study reports the first complete genome sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…In this study, a large outbreak of enteric disease with high morbidity and mortality rates in young kids was associated with GAR infection. These findings are in accordance with previous reports on GAR infection in goats and sheep herds in other countries [7,10,18,19,28,29,31,39] and underscore the relevance of GARs for the livestock industry, chiefly in rural areas. The GAR outbreak occurred in two goat flocks in Kırklareli city, in the Marmara region.…”
supporting
confidence: 94%
“…In this study, a large outbreak of enteric disease with high morbidity and mortality rates in young kids was associated with GAR infection. These findings are in accordance with previous reports on GAR infection in goats and sheep herds in other countries [7,10,18,19,28,29,31,39] and underscore the relevance of GARs for the livestock industry, chiefly in rural areas. The GAR outbreak occurred in two goat flocks in Kırklareli city, in the Marmara region.…”
supporting
confidence: 94%
“…G8P [1] rotaviruses were mainly found in cattle (Ciarlet et al, 1997;Fukai et al, 1999;Okada and Matsumoto, 2002), and rarely reported in other species (Ghosh et al, 2010;Louge Uriarte et al, 2014). Only five cases of G8P [1] strains, all with constellation of genes more similar to animals, were reported in humans, being only three of them detected in children with diarrhea (Banyai et al, 2009a;Ghosh et al, 2011). The sequence and phylogenetic analyzes of the genes analyzed from the 492SR rotavirus-positive sample provides evidence for a direct interspecies transmission animal-to-human, with a potential reassortment with human strains as evidenced by the human-like VP3.…”
Section: Introductionmentioning
confidence: 98%
“…The outer-layer protein is composed of two independent neutralization antigens VP4 and VP7, in which VP4 determines P serotypes and VP7 defines G serotypes. At least 15 G genotypes and 26 P genotypes have been reported [Rao et al, 2000;Ghosh et al, 2011], but G1-G4, G9, P[4], and P[8] are the most prevalent genotypes responsible for RV infections worldwide [Chen et al, 2005;Nguyen et al, 2007;Jin et al, 2009]. In 2006 and 2008, two RV vaccines have been recommended for routine immunization programs of infants in the US.…”
Section: Introductionmentioning
confidence: 99%